Development and partial validation of a method for the quantification of benzodiazepines and antidepressants in whole blood, serum and urine by liquid chromotography - Tandem mass spectrometry - Pieters, Janke (Division of Forensic Medicine and Toxicology, 2015)
The aim of this project is to develop a single quantification method for certain benzodiazepines, opiates and antidepressants in whole blood, serum and urine by LC-MS/M5 and to consequently validate the analytical method for official use in the Division of Pharmacology at the University of Cape Town.